Raising the stakes: How progressive tax rates affect risk‐taking by pass‐through businesses - Ferguson, Duke; Krupa, Trent J.; Laux, Rick C. (Contemporary Accounting Research, 2025)
Abstract We examine how progressive individual tax rates affect risk‐taking by pass‐through businesses (PTBs). PTBs generate over 60% of US business income and make up roughly 95% of business tax returns, yet there is limited research on how progressive tax rates affect project selection. We study PTBs using the setting of thoroughbred racing and examine how progressive tax rates affect the decision to enter a risky stakes race or a less risky allowance race. This setting provides a unique opportunity to observe the choice between two mutually exclusive projects that differ only in expected payoffs and risk. Using a difference‐in‐differences design surrounding the reduction in progressivity under the Tax Cuts and Jobs Act, we find that investment in stakes races increases in the United States relative to Canada. We find further evidence of a negative relation between progressive tax rates and risk‐taking using a plausibly exogenous shock in progressivity in California and exploiting cross‐sectional variation in the progressivity of state tax rates. Overall, our findings should be of interest to policy‐makers considering changes to progressive rates. Results indicate that increases to progressive tax rates may discourage risk‐taking by the small businesses that drive economic growth.